The prevalence of allergic diseases and related risk factors in 13-14 year-old children living in Malatya (Annals of Medical Research, 2021)
Aim: To determine the prevalence of allergic diseases and related risk factors in 13-and 14- year-old children in Malatya, Turkey.Material and Methods: 13-and 14-year-old students in the province of Malatya were given the questionnaire of International Study of Asthma and Allergies in Childhood (ISAAC) which was validated.Results: 304 (53.5%) of the 568 students were females and the mean age was 13.08±0.27 years. The lifetime prevalence of wheezing, rhinitis and atopic eczema were 11.4%, 36.4% , and 4.9% respectively, while the reported prevalence for the last 12 months were 6.3%, 13.9% and3.9% respectively. The rate of diagnosis by the physician was 6.5% for asthma, 3.9% for allergic rhinitis and 5.1% for atopic dermatitis. When the risk factors related to allergic diseases were examined, the risk factors associated with wheezing were; smoking at home (p = 0.022), parental history of allergic diseases (p =0.012) and cockroaches at home (p = 0.023). Risk factor related to rhinitis is parental history of allergic diseases (p =0.023). Risk factors associated with atopic eczema were female gender (p =0.017) and breast milk intake for less than six months (p =0.034).Conclusion: This study is the first to investigate the prevalence of allergic disease in the 13-and 14- age group in Malatya by using the ISAAC questionnaire. The current study shows that the prevalence of allergic diseases is not low in children who are living in Malatya. Keywords: Asthma; Eczema; ISAAC; Prevalence; Rhinitis.
Keywords: key.br /Material and Methods: 13-and 14-year-old students in the province of Malatya were given the questionnaire of International Study of Asthma and Allergies in Childhood (ISAAC) which was validated.br /Results: 304 (53.5%) of the 568 students were females and the mean age was 13.08±0.27 years. The lifetime prevalence of wheezing, rhinitis and atopic eczema were 11.4%, 36.4% , and 4.9% respectively, while the reported prevalence for the last 12 months were 6.3%, 13.9% and3.9% respectively. The rate of diagnosis by the physician was 6.5% for asthma, 3.9% for allergic rhinitis and 5.1% for atopic dermatitis. When the risk factors related to allergic diseases were examined, the risk factors associated with wheezing were; smoking at home (p = 0.022), parental history of allergic diseases (p =0.012) and cockroaches at home (p = 0.023). Risk factor related to rhinitis is parental history of allergic diseases (p =0.023). Risk factors associated with atopic eczema were female gender (p =0.017) and breast milk intake for less than six months (p =0.034).br /Conclusion: This study is the first to investigate the prevalence of allergic disease in the 13-and 14- age group in Malatya by using the ISAAC questionnaire. The current study shows that the prevalence of allergic diseases is not low in children who are living in Malatya. br / Asthma; Eczema; ISAAC; Prevalence; Rhinitis.